2020
DOI: 10.1002/lary.28528
|View full text |Cite
|
Sign up to set email alerts
|

Five‐ and 10‐Year Outcomes for Primary Endoscopic Dacryocystorhinostomy: Failure Rate and Risk Factors

Abstract: Introduction Endoscopic dacryocystorhinostomy (eDCR) is the preferred approach for nasolacrimal duct obstruction, yet quality data on long‐term outcomes is lacking. Study Design A retrospective study in a single, academic institution. Objective To assess the 5‐ and 10‐year success rates of eDCR, and its associated risks. Patients and Methods All eDCRs conducted at Kaplan Medical Center between the years 2002–2017 were included. For long‐term follow‐up analysis, two subgroups with a minimum of documented 5‐ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
3
14
0
2
Order By: Relevance
“…2). The reduced slope over the years resembles our results for primary END‐DCR in a previous study 18 and could be explained by the fact that the risk for stenosis is higher in the first few years and decreases over time 40 . The reduction of success rates over time may serve as an important tool while discussing surgery outcomes with the patients.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…2). The reduced slope over the years resembles our results for primary END‐DCR in a previous study 18 and could be explained by the fact that the risk for stenosis is higher in the first few years and decreases over time 40 . The reduction of success rates over time may serve as an important tool while discussing surgery outcomes with the patients.…”
Section: Discussionsupporting
confidence: 80%
“…Although these success rates are similar to previous studies (Table IV), this is the first study to define its cohort by a minimum follow‐up of 5 years. Compared with our data on primary END‐DCR success rates, 18 we found comparable immediate success rates (92.5% for primary vs. 93.3% for revision), yet significantly reduced long‐term success rates (86.3% for primary vs. 68.9% for revision). Primary surgery did not affect surgical success or patient satisfaction of the surgery.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…These factors may affect the difference in the time for symptom resolution between the very early EnDCR group and the early EnDCR group. Recently, Cohen et al [ 19 ] found that smoking was associated with long-term surgical failure in EnDCR. However, in this study, since the number of smokers was too small for statistical comparison, it was not able to reveal the effects of smoking on the surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%